Emerging Trends in and Strategies for Industry 4.0 During and Beyond Covid-19 - Akkaya, Bülent; Jermsittiparsert, Kittisak; Abid Malik, Muhammad; Kocyigit, Yesim (De Gruyter, 2021)
"Emerging Trends in and Strategies for Industry 4.0 During and Beyond Covid-19" is an all-encompassing scholarly referenced book which is comprised of original and previously unpublished research articles and chapters that would provide cutting-edge, multidisciplinary research and expert insights on advancing technologies and new strategies being used in businesses settings as well as for administrative and leadership roles in organizations during and beyond Covid-19 in perspective of Industry 4.0. The goal of this volume is to provide an overview of how Covid-19 businesses settings as well as for administrative and leadership roles in organizations studies. The Covid-19 outbreak has given an unprecedented shock to the global economy. It has also laid bare the vulnerabilities of many practices that had overtime become defining and sacrosanct features of our economic systems. In particular, business management and administrative have come under scrutiny as different production facilities are closed down, demand patterns shifted, and mobility of goods came to a virtual halt. Concerns have been noted about overreliance on firms to meet even the most basics of our needs. Disruptions caused by the Covid-19 outbreak to supply needs of customers have inflicted immense hardships upon firms and communities globally. It is incumbent upon management scholars to reflect upon this distressful situation, develop knowledge and devise strategies to help overcome the crisis. The world was already moving towards industry 4.0, but the global pandemic of Covid-19 has really rushed the things up. In different aspects of life in general and business in particular, optimized computerization, digitalization and artificial intelligence are being used with never seen- before speed and impact. It has brought with it unique challenges and opportunities. This book looks into the challenges and business opportunities in industry 4.0, trends it is setting, and research and strategies for its successful implementation. Covering a wide range of topics including community engagement, human resource management, data management, economy, R&D, communication, agile production, organizational behaviours and mobile learning, this publication provides insights into technological advancements with business administrative applications and examines forthcoming implementation strategies.